Flu vaccination among older persons: study of knowledge and practices - Gazibara, Tatjana (J Health Popul Nutr, 2019)
BACKGROUND: Surveys of older adults’ knowledge relative to flu immunization have highlighted its relevance in the improvement of vaccination coverage. The purpose of this study was to estimate the proportion of older persons who have ever been immunized against seasonal flu in the municipality of Vračar (Belgrade, Serbia), assess their knowledge related to flu and flu vaccination, and to determine factors associated with flu immunization. METHODS: In the period November 2012–January 2013, 480 persons aged above 65 years were recruited at the Community Health Center, of which 354 persons were finally included in the study. Data were collected using a questionnaire. To assess the level of knowledge, correct answers were awarded 1 point. The total knowledge score ranged from 0 to 17 and was divided into three levels: poor (0–4 points), moderate (5–8 points), good (9–13 points), and excellent (14–17 points). RESULTS: The proportion of ever vaccinated older persons was 47.7%. Of those, one third (29.1%) had been immunized regularly. Most seniors (61.9%) demonstrated good, whereas one third (29.8%) demonstrated excellent level of knowledge. In terms of reasons for non-compliance, the highest proportion of older persons declined vaccination because “they were in good health” (33.5%) and because “they did not believe that vaccine protects from flu” (31.5%). Independent predictors of being ever immunized against seasonal flu were having higher level of education, being more knowledgeable relative to flu vaccination, and taking more medications. CONCLUSIONS: Our results indicate that health care sector requires well-coordinated promotion campaigns to enhance acceptance of flu vaccination. Organized immunization counseling could provide accurate, evidence-based information in order to transform misbeliefs, prejudice, and negative attitude towards vaccination. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s41043-018-0159-8) contains supplementary material, which is available to authorized users.